Protective effect of a natural herb (Rosmarinus officinalis) against hepatotoxicity in male albino rats - Abdel-Wahhab, Khaled Gamal El-Deen; El-Shamy, Karima Abbas; El-Beih, Nadia Abd El-Zizz; Morcy, Fatma Adly; Mannaa, Fathia Abd Elwahid (Federal University of Piauí, 2011)
The present study was conducted to study the chemoprotective effect of Egyptian rosemary extract (RE) against CCl4-induced hepatotoxicity. Eight experimental groups were used as follow: (1) control; (2&3) RE alone (440 mg/kgb.w) for 4 and 8 weeks, respectively; (4) CCl4 (1ml/kg b.w, twice a week, i.p) for 4 weeks; (5&7) RE (220&440 mg/kg) for 4 weeks before CCl4 for a similar period; and (6&8) RE (220&440 mg/kg) for four weeks before CCl4 in combination with RE another four weeks. The sequential CCl4 treatment induced significant changes in serum biochemical parameters accompanied by sever histological and histochemical changes of the liver tissue, while administration of 440 mg/kg/day for either 4 or 8 weeks did not induce any changes. Administration of RE before or during the treatment with CCl4 improved all biochemical parameters and histological picture of the liver, in a dose and duration-dependant manner. It could be concluded that RE has a protective effects against hepatotoxicity.